2019
DOI: 10.1088/1361-665x/ab28ed
|View full text |Cite
|
Sign up to set email alerts
|

A sparse self-estimated sensor-network for reconstructing moving vehicle forces

Abstract: Reconstructing moving vehicle forces from structural responses is an important inverse problem in bridge engineering. When a sensor-network is applied to moving force identification (MFI), a necessary task is to specify the contribution of different sensors at the first beginning. This paper proposes a novel method based on the sparse self-estimated sensor-network for estimating moving vehicle forces on bridges. Firstly, an over-completed dictionary is pre-defined to ensure a sparse representation of moving ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Chen, Qin et al, 2019;Z. Chen & Chan, 2017;Feng et al, 2015;Liu et al, 2020;C.-D. Pan et al, 2017;C.-D. Pan et al, 2018;C. Pan et al, 2019;Zhong et al, 2019; X. Q.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Chen, Qin et al, 2019;Z. Chen & Chan, 2017;Feng et al, 2015;Liu et al, 2020;C.-D. Pan et al, 2017;C.-D. Pan et al, 2018;C. Pan et al, 2019;Zhong et al, 2019; X. Q.…”
Section: Introductionunclassified
“…Pan et al., 2017; C.‐D. Pan et al, 2018; C. Pan et al, 2019; Zhong et al., 2019; X. Q. Zhu & Law, 2016). Nevertheless, the practical application of MFI methods is still limited as it requires the information on the dynamic properties of the bridge that is difficult to accurately estimate (Yu et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The vehicle and bridge systems are coupled at the contact points. It is a typical moving load problem and extensive research has been conducted on the moving force identification techniques to quantify the interaction via measurements from the bridge [17][18][19]. O'Brien et al [20] identified the interaction forces from vehicle dynamic responses.…”
Section: Introductionmentioning
confidence: 99%